IMPLICATIONS OF HALAL TOURISM SECTOR TO OPTIMIZE REGIONAL OWN SOURCE REVENUE OF TAX AND TOURISM CHARGES IN EAST LOMBOK REGENCY - et al., Fadjar Harimurti (International Journal of Advanced Science and Technology, 2019)
The conduction of the present study was motivated by proliferation of authority of Regional Government regarding the enactment of a Regional Regulation on tourism which is not followed by a synchronized functions. All involved parties had a strong argument in defending a religious regulation, thus, it consequently led to a multi-interpreted, conflictual and disobedient legal situations which created a disharmony between one and other rules. The type of the present study is a normative legal research. It emphasizes literature study with the focus of the research in principles of law, systematics of law, synchronization of law and legal history. Besides, this was also a descriptive research. The conclusions of the present study are, (1) the decentralization of tourism management gave authority to the Regional Government in forming legal products to increase Regional Own-source Revenue, (2) the Regional Government of West Nusa Tenggara Province needs to pay more attention to the principles and basis of lex superior derogat legi inferiori in establishment of the West Nusa Tenggara Province Regulation No. 2 Year 2016 concerning Halal Tourism. This can be seen from the material regulated in the Regional Government Regulation which had a religious nuance, so that Halal tourism did not maximally contribute to the Regional Own-source Revenue in recreation and sport center charges.